Temporally varied coastal uplift rates north of the Littoral Fault Zone since the late Quaternary in the northern South China Sea: Insights from the wave-cut platform and cosmogenic exposure dating - Liang, Hao; Zhang, Ke; Li, Zhigang; Chen, Zhen; Hui, Gege; Huang, Ping; Tian, Qingying; Tang, Yongjie; Chen, Cong; Zhang, Yipeng; He, Xiaohui; Yan, Yonggang; et al. (Frontiers in Earth Science, 2023)
Understanding the long-term slip rate of active normal faults is essential for the comprehensive assessment of seismic activity but is difficult due to the absence of age control in the erosional bedrock region. The preserved sequence of wave-cut platforms in granite allows for exploring the long-term slip rate that occurs in the footwall of some normal faults. We investigate wave-cut platforms in the southern Pearl River Delta (PRD), a coastal delta transected by the seismically active Littoral Fault Zone (LFZ) in the northern South China Sea, to derive slip rates and their impacts on the seismic hazard potential. We have mapped a flight of four wave-cut platforms (T1–T4), dated the T2 and T4 platforms by 10Be cosmogenic nuclide dating, and used the absolute age to correlate the un-dated platform with global sea-level highstands. Our results allocate ages of 128 ka, 197 ka, and 239 ka to the upper three wave-cut platforms, and yield temporally various uplift rates ranging from 0.30–0.38 mm/a during 239–128 ka to 0.09 mm/a since 128 ka. A decrease in the uplift rate, which coincides with a decreased subsidence rate within the PRD in previous work, implies a weakened differential uplift onshore of the LFZ system. Our findings infer that the transgression event occurred as early as marine isotope stage (MIS) 7 in the PRD, consistent with the view that Pleistocene sedimentation began in MIS 5 or possibly even earlier in the PRD.